Human endogenous retrovirus expression profiles in samples from brains of patients with schizophrenia and bipolar disorders - Frank, Oliver; Giehl, Michelle; Zheng, Chun; Hehlmann, Rüdiger; Leib-Mösch, Christine; Seifarth, Wolfgang (Journal of virology, 2005)
The detection and identification of retroviral transcripts in brain samples, cerebrospinal fluid, and plasma of individuals with recent-onset schizophrenia and schizoaffective disorders suggest that activation or upregulation of distinct human endogenous retroviruses (HERVs) may play a role in the etiopathogenesis of neuropsychiatric diseases. To test this hypothesis, we performed a comprehensive microarray-based analysis of HERV transcriptional activity in human brains. We investigated 50 representative members of 20 HERV families in a total of 215 brain samples derived from individuals with schizophrenia or bipolar disorders and matched controls. A characteristic brain-specific retroviral activity profile was found that consists of members of the class I families HERV-E, HERV-F, and ERV9 and members of HERV-K taxa. In addition to these constitutively expressed HERVs, a number of differentially active HERV elements were identified in all brain samples independent of the disease pattern that may reflect differences in the genetic background of the tested individuals. Only a subgroup of the HML-2 family (HERV-K10) was significantly overrepresented in both bipolar-disorder- and schizophrenia-associated samples compared to healthy brains, suggesting a potential association with disease. Real-time PCR analysis of HERV env transcripts with coding capacity potentially involved in neuroinflammatory conditions revealed that env expression of HERV-W, HERV-FRD, and HML-2 remains unaffected regardless of the clinical picture. Our data suggest that HERV transcription in brains is weakly correlated with schizophrenia and related diseases but may be influenced by the individual genetic background, brain-infiltrating immune cells, or medical treatment.